FREQUENCY OF PATHOGENS ISOLATED IN CLINICAL CASES OF CANINE PIODERMA AND ITS ANTIMICROBIAL SUSCEPTIBILITY - Antúnez A., Oscar (2009)
The canine bacterial dermatitis, commonly known as pyoderma is one of the main skin diseases in the veterinary practice. The present retrospective study had the objective to determine the frequency of the bacteriological agents involved with the disease and the antibiotics that show better antimicrobiobial susceptibility. Laboratory records of bacterial isolation and antibiogram of the Laboratory of Bacteriology of the Veterinary Medicine Faculty, San Marcos University, Lima, were analyzed. Staphlococcus intermedius was the most commonly isolated species (70.6%). The most effective antibiotics were from the Cephalosporin family, especially the ceftiofur and cefalexin, and penicillin was the antibiotic with higher resistance index.